Developing an integrated policy for the maritime and coastal heritage of the UAE: a collaborative approach - Blue, Lucy; Strutt, Kristrian; Sheehan, Peter; Jackson, Peter; Beech, Mark (Proceedings of the Seminar for Arabian Studies, 2013)
This paper explores a vision to build capacity and establish an integrated policy for the maritime and coastal heritage of the UAE through the case study of a collaborative coastal survey project. It is recognized that currently none of the GCC (Gulf Cooperation Council) countries has maritime heritage legislation, and there is limited specific maritime expertise within the ministries responsible. In October 2011 the first phase of the Coastal Heritage Project of the UAE was conducted between the Abu Dhabi Authority for Culture and Heritage (ADACH), now known as Tourism and Cultural Authority Abu Dhabi (TCA Abu Dhabi), the Directorate of Heritage Sharjah (Rulers Office/Historic Buildings), the Maritime Archaeological Stewardship Trust (MAST), and Archaeological Prospection Services of Southampton (APSS), at two targeted sites in the UAE. A comprehensive magnetometer survey was conducted on selected areas on Delma Island, Abu Dhabi and of the entire site of Al Khan, Sharjah. Sections of the historic waterfront towns at both sites were surveyed using ground-penetrating radar (GPR), and an initial survey of a series of historic fish traps on the western shore of Delma Island was conducted. The results have generated further collaboration with other Emirates with the intention of conducting similar surveys at other coastal sites of the UAE in 2012 and collating integrated data sets. Workshops are also planned to provide the necessary training in geophysical and maritime techniques for regional heritage departments. This project is the first step towards capacity building, collaboration, and the sharing of expertise in the region.